Innovation in Furudhul Ainiyah Learning in Islamic Boarding Schools: The Learning-by-Doing Approach as a Solution for Understanding the Material - Fathor Rozi; Faikotul Hikmah; Khodijatul Qodriyah (Muróbbî: Jurnal Ilmu Pendidikan, 2026)
Learning Furudhul Ainiyah in Islamic boarding schools often experiences obstacles in terms of students' understanding due to the dominance of theoretical teaching methods. This study aims to examine the effectiveness of the learning-by-doing approach as a solution to improve understanding of Furudhul Ainiyah material at the Nurul Jadid Islamic Boarding School, specifically in the Al-Hasyimiyah area of Al-Masruriyah. The method used is a qualitative approach with a case study type through data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the direct practice approach is able to increase the active involvement of students in the learning process, strengthen their understanding of basic fiqh materials, and foster a religious attitude through continuous internalization of values. Data visualization from interviews, observations, and documentation shows that changes in methods have an impact on more active, systematic, and measurable learning behavior patterns. Practice-based learning has been shown to bridge the gap between religious knowledge and practice in Islamic boarding schools. These findings suggest that learning by doing can be an alternative, more contextual, participatory, and transformative learning strategy.